Determinants of generation Y actual purchasing of organic coffee: A SEM-PLS approach - Tinneke Hermina; Hanifah Fauziah (International Journal of Artificial Intelligence Research, 2022)
Environmental issues have now become a global problem, which requires people to try to be more aware and integrate environmentally friendly aspects into their daily lives. Each agenda in the SGDs has goals and objectives related to humanity because the basic goals of sustainable development have a foundation, namely people, planet, prosperity, peace, and partnership. The MSME sector that contributes to preserving the environment to reduce environmental issues is the MSME Coffee sector. The contribution of MSME Coffee in preserving the environment is by utilizing coffee husks as compost. The quantitative research method adopts a descriptive approach to describe the situation to be studied with support in the form of literature studies to strengthen the results of the researcher's analysis in conclusion. In addition, the verification method to test the truth of the hypothesis is carried out by collecting data in the field to analyze the relationship of each variable. The results of the study explain that respondents have morals because they have a sense of responsibility to the environment as millennial consumers. The form of concern for the environment is done by changing consumption patterns, namely buying environmentally friendly coffee.